(untitled) (Journal of Pharma Insights and Research, 2025)
The rapid evolution of artificial intelligence (AI) technologies provides numerous possibilities for science education, particularly in biology instruction at the secondary level. This study investigated the perceptions of biology teachers regarding AI integration in secondary schools within Ilorin-West Local Government Area, Kwara State, Nigeria. The research employed a descriptive survey design with a sample of 71 biology teachers selected through systematic sampling. Data collection utilized a structured questionnaire focusing on perceived benefits and consequences of AI integration in biology education. The study considered teachers’ gender, qualifications, and teaching experience as moderating variables. Results indicated that teachers strongly recognized AI’s potential for personalizing learning experiences (Mean = 3.57) and creating interactive biology lessons (Mean = 3.24). However, significant concerns emerged regarding the reduction of traditional teaching roles (Mean = 3.27) and ethical implications of AI implementation (Mean = 3.13). Statistical analyses revealed no significant differences in perceptions based on gender (t(68) = 1.45; p > .05), qualifications (t(68) = -0.54; p > .05), or teaching experience (F(2,67) = 0.04; p > .05). The results indicate a collective understanding among biology teachers regarding AI’s educational value, while indicating the need for structured professional development programs to optimize AI integration in biology instruction